PENGARUH SOSIAL BUDAYA, LATAR BELAKANG PENDIDIKAN, PENGALAMAN KERJA, DAN MOTIVASI KERJA TERHADAP ETOS KERJA KARYAWAN BANK SYARIAH INDONESIA KCP TULUNGAGUNG SUDIRMAN - Solekhah, Fina (Fakultas Ekonomi dan Bisnis Islam, 2022)
This study aims to determine the effect of the socio-cultural, educational background, work experience, and work motivation on the work ethic of employees of Bank Syariah Indonesia KCP Tulungagung Sudirman, both partially or simultaneously. This research method is a quantitative study, the research sample is all employees of Bank Syariah Indonesia KCP Tulungagung Sudirman, totaling 28 employees. The sampling technique used is non-probability sampling using a saturated sample technique, where all the population is sampled. Data collecting using a questionnaire that has been tested for validity and reliability. The data analysis method used multiple linear regression analysis using of SPSS 16.0 software. The results showed that partially socio-cultural had a positive and insignificant effect on work ethic, educational background had a negative and insignificant effect on work ethic, work experience had a positive and significant effect on work ethic, and work motivation had a positive and significant effect on work ethic. Meanwhile, it is simultaneously stated that socio-cultural, educational background, work experience, and work motivation simultaneously affect the work ethic of BSI KCP Tulungagung Sudirman employees.